Pancreatic satellite cells derived galectin-1 increase the progression and less survival of pancreatic ductal adenocarcinoma. - Dong Tang; Jingqiu Zhang; Zhongxu Yuan; Jun Gao; Sen Wang; Nianyuan Ye; Ping Li; Sujun Gao; Yi Miao; Daorong Wang; Kuirong Jiang (PLoS ONE)
Background Galectin-1, a member of carbohydrate-binding proteins with a polyvalent function on tumor progression, was found strongly expressed in pancreatic satellite cells (PSCs), which partner in crime with cancer cells and promote the development of pancreatic ductal adenocarcinoma (PDAC). We evaluated the effects of PSCs derived Galectin-1 on the progression of PDAC, as well as the tumor establishment and development in mouse xenografts. Methods The relationship between immunohistochemistry staining intensity of Galectin-1 and clinicopathologic variables were assessed in 66 PDAC tissues, 18 chronic pancreatitis tissues and 10 normal controls. The roles of PSCs isolated from PDAC and normal pancreas on the proliferative activity, MMP2 and MMP9 expression, and the invasion of CFPAC-1 in the co-cultured system, as well as on the tumor establishment and development in mouse xenografts by mixed implanting with CFPAC-1 subcutaneously were evaluated. Results Galectin-1 expression was gradually increased from normal pancreas (negative), chronic pancreatitis (weak) to PDAC (strong), in which Galectin-1 expression was also increased from well, moderately to poorly differentiated PDAC. Galectin-1 staining intensity of pancreatic cancer tissue was associated with increase in tumor size, lymph node metastasis, perineural invasion and differentiation and UICC stage, and served as the independent prognostic indicator of poor survival of pancreatic cancer. In vitro and in vivo experiments indicated that TGF-β1 upregulated Galectin-1 expression in PSCs, which could further promotes the proliferative activity, MMP2 and MMP9 expression, and invasion of pancreatic cancer cells, as well as the tumor establishment and growth. Conclusion Galectin-1 expression in stromal cells of pancreatic cancer suggests that this protein plays a role in the promotion of cancer cells invasion and metastasis and provides a therapeutic target for the treatment of pancreatic cancer.